Bubble dynamic wave velocity in fluidized bed. (22nd June 2016) - Wei, Liping; Lu, Youjun
Abstract: Experimental and numerical investigations have validated that the supercritical water (SCW) fluidized bed has bubbling fluidization state, which obviously diverges from the classical gas–solid fluidized bed. It is difficult to apply the classical bubbling parameters including diameter and rising velocity to characterise the bubbles within the SCW fluidized bed due to the unattainable measurements in the high temperature and pressure conditions. This paper derived bubble dynamic wave (BDW) velocity to establish a theoretical description of the bubbling characteristics for different bubbling systems. The BDW velocity is a propagation velocity of interface wave between bubble and emulsion phase induced by the perturbation of bubble volume. The expression of the BDW velocity was derived by treating emulsion phase as compressible fluid. The BDW velocity of the SCW fluidized bed (intermediate fluidization) shows an intermediate value between air or steam–solid system (classical bubbling fluidization) and ambient water–solid system (classical homogenous fluidization). Further, the BDW energy was derived to characterise the fluid dynamic in meso-scale. The variation trend of BDW energy with superficial velocity was consistent with that of the measured meso-scale energy of differential pressure fluctuation signals. This paper provided a new parameter of BDW velocity for describing the characteristics of bubbling fluidized bed. Graphical abstract: The bubble dynamic wave (BDW) velocity could characterise the bubble characteristics of different fluid-solid system and transformations form a homogeneous fluidization to intermediate and then to bubbling fluidization, as shown in Fig. 1. The BDW velocity in supercritical water (SCW) fluidized bed is an intermediate velocity between the ambient and high-pressure water-solid system (classical homogeneous system) and steam or air-solid system (classical the bubbling system), which indicates the SCW fluidized bed is an intermediate fluidization. Highlights: A new concept of bubble dynamic wave velocity was proposed. The expression of bubble dynamic wave velocity was derived. Bubble dynamic wave velocity can characterize different bubbling systems.